Gerakan Penguatan Kapasitas Kelembagaan Nadhlatul Ulama Ranting Gapura Timur (LPTNU Sumenep, 2022)
In this study, we will focus on the Movement for Strengthening the Institutional Capacity of Nadhlatul Ulama of the East Gapura Branch. Nadhlatul Ulam Gapura Timur who continues to strive for institutional strengthening with a cultural and structural approach as a basis for strengthening at NU Gapura Timur. This research was conducted in order to make NU Gapura Timur's organization more advanced so that the intention to build an office could be achieved. This research is a field research (Field research) in the form of qualitative and literature by collecting data, as well as researching references related to the subject being studied, both papers, books, newspapers, journals, papers as well as interviews using a sociological approach, which means conducting a study of social facts in the village of East Gapura by looking at the theoretical framework used in analyzing data or facts, which revolves around the problems faced related to the institutional strengthening movement. The result is that the Nadhatul Ulama Institutional Strengthening Movement of the East Gapura branch is able to build a synergy between cultural and structural, build awareness of the importance of organization and is able to make the daily administrators of Nadhlatul Ulama Gapura Timur stronger and more independent.